Finding ‘the inner drive’ for a rehabilitation process: a small-scale qualitative investigation among male patients with primary glioma - Mette Lysdahl Fahrenholtz; Anders Hansen; Karen Søgaard; Lotte Nygaard Andersen (BMJ Open)
Objective Brain tumours are relatively rare but hold a significant place in cancer rehabilitation due to their pronounced disabling capacity to promote physical, cognitive and psychosocial sequelae. This small-scale qualitative study used coping and motivational theories to gain understanding and knowledge of patients’ experience of being diagnosed with a severe disease and of their view of a rehabilitation process.Design Qualitative interview study.Setting Odense University Hospital, Denmark.Informants Five patients (men, aged 30–79 years) with primary glioma who had participated in a rehabilitation intervention.Methods Semi-structured interviews were conducted. The phenomenological interpretive analysis was used to analyse the interviews.Results The analysis revealed three main themes: (1) coping with a new life situation, (2) motivating and maintaining elements and (3) experience of the benefit of the rehabilitation programme.Conclusion The study concluded that interviewed informants use problem-solving coping strategies, which make them more active in their health behaviour. However, passive and emotion-focused strategies related to confronting diagnosis may be used in some cases. The motivational aspect is multifaceted. Personal and interpersonal elements alongside a competitive setting are crucial to self-efficacy and benefit. The intervention’s impact on health-related quality of life also has the potential to increase patients’ resources to manage their situation.Trial registration number NCT02221986